Green Tea Polyphenol Epigallocatechin Gallate Interactions with Copper-Serum Albumin - Meiling Fu; Liangliang Zhang; Rick Killeen; Kenneth E. Onugwu; Robert M. McCarrick; Ann E. Hagerman (Molecules)
Epigallocatechin gallate (EGCg), an abundant phytochemical in green tea, is an antioxidant that also binds proteins and complex metals. After gastrointestinal absorption, EGCg binds to serum albumin in the hydrophobic pocket between domains IIA and IIIA and overlaps with the Sudlow I site. Serum albumin also has two metal binding sites, a high-affinity N-terminal site (NTS) site that selectively binds Cu(II), and a low-affinity, less selective multi-metal binding site (MBS). We proposed to determine whether EGCg binds or reacts with Cu(II)-serum albumin using fluorescence, UV–Visible and electron paramagnetic resonance (EPR) spectroscopy. Our results suggest that when serum albumin is loaded with Cu(II) in both sites, EGCg binds to the MBS-Cu(II) and reduces the copper to Cu(I). EGCg does not bind to or react with Cu(II) in the high-affinity NTS site. Potential consequences include changes in copper homeostasis and damage from pro-oxidative Fenton reactions.